A disposable electrochemical sensor based on iron molybdate for the analysis of dopamine in biological samples. (15th June 2021) - Kumar, Elumalai Ashok; Chen, Tse-Wei; Chen, Shen-Ming; Wang, Tzyy-Jiann; Anthuvan, Allen Joseph; AlOmar, Suliman Yousef; Ahmad, Naushad; Chang, Yu-Hsu
Abstract : Developing cost-effective approaches for the fabrication of electrochemical devices is instantly needed for transferring from basic research to point-care technology. Abstract : Developing cost-effective approaches for the fabrication of electrochemical devices is instantly needed for transferring from basic research to point-care technology. Herein, we report an electrochemical sensing platform based on an iron molybdate (Fe2 (MoO4 )3 )-modified screen-printed carbon electrode (SPCE) for the sensitive and selective sensing of dopamine (DA). The formation and purity of Fe2 (MoO4 )3 was characterized via multiple spectroscopic techniques. Likewise, the electrochemical performance of the Fe2 (MoO4 )3 modified SPCE was probed via cyclic voltammetry and differential pulse voltammetry. Fe2 (MoO4 )3 /SPCE exhibited a 1.44-fold increase in electrochemical sensing activity towards DA than bare SPCE. In a range as wide as from 0.01 to 225 μM, a linear relationship is well established with the value of correlation coefficient being 0.9914. The limit of detection (S/N = 3) is well defined as 0.002 μM, which is lower than that reported previously. The fabricated Fe2 (MoO4 )3 /SPCE shows good anti-interference ability towards DA detection in the presence of numerous co-interfering compounds at a higher level. Moreover, a biological analysis indicated that spiked DA can be determined accurately by Fe2 (MoO4 )3 modified SPCE with the recovery rate in the range of 99.30–99.80% in human serum samples. Based on the above-mentioned results, the proposed electrochemical sensor has great potential in the fields of biological detection.